Czech Reformational biblical translation: the case of pericopes in the Unity of the Brethren in the 1550s‒1570s - Dittmann, Robert (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The pericopes in vernacular languages were one of the achievements of the European Reformation. In Bohemian Lands, the pericopes were read in Czech already soon after 1415, namely as a feature of the Hussite movement. Fully Bohemicised liturgy, thus promoting Czech as the first vernacular within the Roman obedience to holy languages, was adopted by the Unity of the Brethren. The development of pericopes within the Unity was dynamic and noteworthy. The study describes and by textual probes illustrates the development of pericopes in the Unity after the reform of Lukas of Prague, which is tightly connected to the most literal Czech biblical translation in the 16th century, published in 1525. In the 1540s, the bishop Jan Augusta attempted at a reform of the pericopal system and in his Summovník he translated pericopes rather literally from Biblia Tigurina. His translation was modified by other Brethren bishops and printed in 1557‒1559. A new revised version came out in 1563 but no copy has survived. In 1571 Blahoslav’s Evanjelia and in 1575 Štefan’s Postil were published, both including pericopes. The study explores in detail the mutual textual relations of these prints.